Bulk sedimentary phosphorus in relation to organic carbon, sediment textural properties and hydrodynamics in the northern Beibu Gulf, South China Sea. (June 2020) - Dan, Solomon Felix; Lan, Wenlu; Yang, Bin; Han, Lijun; Xu, Cheng; Lu, Dongliang; Kang, Zhenjun; Huang, Haifang; Ning, Zhiming
Abstract: Bulk sedimentary phosphorus (P) is studied to evaluate its source, distribution, preservation and enrichment in relation with organic carbon (OC), sediment textures and moisture contents in the northern Beibu Gulf. Approximately 80% of surface sediments in the investigated sites were composed of coarse sandy texture (>63 μm). Total P (TP), inorganic P (IP) and organic P (OP) contents were lower to medium range compared to the levels reported for other marginal seas. Sedimentary OC and P were derived from mixed sources, with high terrestrial influence in the coastal areas (molar OC/OP ratios >250:1). The distribution of P corroborated with the variation tendency of fine-grained sediments, moisture contents and OC. Both IP and OP may significantly influence the trophic state of seawater if released from surface sediments. Influenced by hydrodynamics, frequent resuspension and high abundance of sand, TP is less preserved, and shows low to moderate enrichment in surface sediments. Highlights: Approximately 80% of the deposited sediments were predominated by coarse sand. Sedimentary TP was mostly composed of IP, with elevated OP in some coastal sites. Lower (<1%) OC contents in many sites suggested possible remineralization. Coastal sites with molar OC/OP >250:1 indicated terrigenous OC and OP source. Sedimentary P enrichment, and OC were influenced by different environmental factors.